Modeling effective interface laws for transport phenomena between an unconfined fluid and a porous medium using homogenization - Jäger, Willi; Mikelić, Andro (Transport in porous media, 2009)
In this chapter of the special issue of the journal "Transport in Porous Media", on the topic "Flow and transport above permeable domains", we present modeling of flow and transport above permeable domains using the homogenization method. Our goal is to develop a heuristic approach which can be used by the engineering community for treating this type of problems and which has a solid mathematical background. The rigorous mathematical justification of the presented results is given in the corresponding articles of the authors.